1996
DOI: 10.3168/jds.s0022-0302(96)76593-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bovine Somatotropin Administered to Periparturient Dairy Cows on the Incidence of Metabolic Disease

Abstract: Thirty-eight dry, pregnant Jersey cows were assigned to diet and bST treatment in a 2 x 2 factorial design. During the dry period, half of the cows were fed a normal TMR (0.4% Ca; 0.3 to 0.4% P), and half of the cows were fed a high Ca TMR (1.5 to 1.6% Ca; 0.4 to 0.7% P). The high Ca diets were designed to induce milk fever and were relatively cationic (194 to 293 meq/kg) compared with the normal diets (-131 to 30 meq/kg). A standard dairy diet was fed to all cows postcalving. Cows received subcutaneous inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Therefore, they concluded that productive efficiency gains with bST occurred because a large portion of the nutrients consumed were diverted for milk synthesis. Consistent with the results in the present study, Eppard et al (1996) did not observe a difference in DMI in lactating dairy cows treated with bST compared with control cows under Tn conditions. Contrary to our findings, West et al (1991) noted a reduction in the DMI of bST-treated dairy cattle exposed to heat stress.…”
Section: Feed Intakesupporting
confidence: 92%
“…Therefore, they concluded that productive efficiency gains with bST occurred because a large portion of the nutrients consumed were diverted for milk synthesis. Consistent with the results in the present study, Eppard et al (1996) did not observe a difference in DMI in lactating dairy cows treated with bST compared with control cows under Tn conditions. Contrary to our findings, West et al (1991) noted a reduction in the DMI of bST-treated dairy cattle exposed to heat stress.…”
Section: Feed Intakesupporting
confidence: 92%
“…Cows treated with 500 mg of rbST every 14 d during the prepartum period had increased DMI and glucose concentration, reduced concentrations of fatty acids and BHB around the time of calving, and greater milk yield in the first 42 d of lactation compared with control cows (Putnam et al, 1999). In contrast, Jersey cows treated with 500 mg of rbST every 14 d from −28 to 14 d postpartum had reduced fat-corrected milk yield (Eppard et al, 1996). Cows treated with 325 mg of rbST every 14 d during the prepartum period had increased glucose concentration during the peripartum period, but no differences in DMI, incidence of postpartum diseases, or reproductive performance were observed (Gohary et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…A low dose of rbST (142.8 mg) given every 14 d from −21 to 42 d postpartum increased peripartum concentrations of IGF-1, glucose, and insulin; increased milk yield; and decreased the incidences of ketosis, mastitis, and digestive problems (Gulay et al, 2003(Gulay et al, , 2004(Gulay et al, , 2007. The effects of rbST treatment of periparturient dairy cows on incidences of retained fetal membranes and metritis are more controversial (Eppard et al, 1996;Putnam et al, 1999;Gulay et al, 2007;Gohary et al, 2014), perhaps because some of the cited experiments lacked appropriate sample size or because of differences in rbST treatment frequency and dose.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that only 2 treatments of rbST given to cows with hyperketonemia was insufficient to cause an increase in blood glucose. However, many studies have found no differences in blood glucose between rbST-treated and control cows (Eppard et al, 1996;Gulay et al, 2003Gulay et al, , 2004b.…”
Section: Blood Analytesmentioning
confidence: 96%